Ventilator-induced Lung Injury: Role of Protein-Protein Interaction in Mechanosensation - Han, B. (Proceedings of the American Thoracic Society, 2005)
For critically ill patients, mechanical ventilation is a commonly used life-supporting modality, but ventilation per se could also induce lung injury. Mechanical forces-induced cell damage and inflammatory responses have been considered as one of major mechanisms of ventilator-induced lung injury (VILI). Mechanotransduction related to VILI has been the subject of several recent reviews, which focused on the mechanical force-induced signal cascades. In this article, we will discuss the initial processes, mechanosensation, by which physical forces can be sensed by the cells and converted into biochemical reactions for intracellular signaling. In addition to suggested mechanosensors, such as stretch-activated ion channels, extracellular matrix-integrin-cytoskeleton complex, and growth factor receptors, we would like to introduce a new concept of intracellular mechanosensation through specific protein-protein interactions. Proteins associated with the cytoskeleton could transmit physical forces, and bind with signaling-related enzymes through specific functional domains and motifs. These interactions could lead to activation or inactivation of the enzymes, and subsequently alter the signal transduction processes in the cells. Understanding these mechanisms will help us to develop new strategies for the management of VILI.